Art Déco Sertanejo and a possible revival: the Campina Grande Déco Project - Rossi, Lia Monica (Revista UFG, 2017)
Art Déco Sertanejo: the baptism But why sertanejo? The term sertão (backwoods, hinterland), a Brazilian northeastern geographic region, neighboring the Agreste and Cariri, comes from the colonial Portuguese word desertão (big desert), meaning a region which is distant from urban centers, the backwoods of a country or region, remote, with little civilization. We see it as something beyond its geographic definitions, whether accurate or not. The sertão is also a poetic place. It can express the immensity of the lonely uninhabited semiarid open countryside as well as a piece of land of fond memory, meu (my) sertão2 . It was these real and imaginary backlands which inspired us to give the name Sertanejo to the unregistered Art Déco style of the popular northeastern façades. (...)